Human capital and organisational effectiveness: an analysis into technology-based companies / Hapsah S. Mohammad - S. Mohammad, Hapsah (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
This paper attempts to review the literature on the relationship between human capital and organisational effectiveness particularly in technology-based companies. It highlights that attracting human capital is only part of the process of managing human capital. The steps taken to develop and subsequently retain human capital in an organisation is as crucial as attracting them in the first place. Discussion on human capital is based on the model as suggested by Dess et al (2014). This is a conceptual paper and an effort towards extending the theory of Dess et al. (2014).